Testing a novel bioactive marine nutraceutical on osteoarthritis patients - Catanzaro, Roberto; Lorenzetti, Aldo; Solimene, Umberto; Zerbinati, Nicola; Milazzo, Michele; Celep, Gulcip; Sapienza, Chiara; Italia, Angelo; Polimeni, Ascanio; Marotta, Francesco (Acta Biomedica Atenei Parmensis, 2013)
Osteoarthritis (OA) is a slow, chronic joint disease characterized by focal degeneration of articular cartilage and alterations of the chemical and mechanical articular function and also major cause of pain and physical disability. There is clinical evidence that increasing dietary n-3 relative to n-6 may be beneficial in terms of symptom management in humans but not all studies conclude that dietary n-3 PUFA supplementation is of benefit, in the treatment of OA. Our recent studies highlight the effect of a biomarine compound (LD-1227) on MMPs, collagen metabolism and on chondrocyte inflammatory markers. Thus, the aim of the present work was to test such bioactive compound versus a common nutraceutical intervention (glucosamine/chrondroitin sulfate) in knee osteoarthritis patients. The patients population consisted of 60 subjects with a recent diagnosis of knee osteoarthririts of mild-moderate severity. Patients were randomized in a double-blind study comparing LD-1227 (group A) versus a mixture of glucosamine (500 mg), chondroitin sulfate (400 mg) (group B). Patients were allowed their established painkillers on demand. At 4, 9 and 18 weeks patients were evaluated as for: VAS score assessing pain at rest, and during physical exercise, Lequesne index, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scale and KOOS scale. Moreover, serum concentrations of IL-6, IL-β, CRP, TNF-sR1 and TNF-sR2 were assessed. As compared to GC treatment, LD-1227 yielded a quicker and higher degree of improvement of the whole clinical indexes and a lower NSAIDs use at the end of the study. LD-1227 brought about also a more significant downregulation of the tested cytokines cascade. Taken overall, these data suggest that LD-1227 has the potential to be included in the nutraceutical armamentarium in the management of OA.